2016
DOI: 10.1136/bmjopen-2016-013479
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among medical students in Southern Thailand: a mixed methods study

Abstract: ObjectivesThe study aimed to investigate the prevalence of physical activity (PA) and factors influencing PA behaviours among medical students in Southern Thailand.DesignThe study implemented a mixed methods approach. The sequential design consisted of 2 phases: a survey followed by in-depth interviews.SettingThe study was conducted in the 3 campuses of a medical school in Southern Thailand. The preclinical students (years 1–3) studied general and basic science subjects at Nakhon Si Thammarat campus. The clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 23 publications
5
61
2
4
Order By: Relevance
“…on practice of physical activity among future doctors showed that, physical activity was more among boys as compared to girls i.e 62% versus 38%. In a study by Apichai Wattanapisit et al [4] , also it was found that preclinical students and male sex were the factors associated with more physical activity. Their study also points to the fact taht being a medical student was a risk of physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…on practice of physical activity among future doctors showed that, physical activity was more among boys as compared to girls i.e 62% versus 38%. In a study by Apichai Wattanapisit et al [4] , also it was found that preclinical students and male sex were the factors associated with more physical activity. Their study also points to the fact taht being a medical student was a risk of physical inactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Being physically active is an important component of a healthy lifestyle (49). Therefore, medical students, who will be the future physicians, should maintain their physical activity to keep healthy and continue as role models for their patients and to be able to motivate them regarding physical activity (50).…”
Section: Discussion:-mentioning
confidence: 99%
“…In Thailand, Wattanapisit et al (49) reported that less than half of the participants (49.5%) were physically active.…”
Section: High 22 (13%)mentioning
confidence: 99%
“…Male and preclinical students were more likely to be physically active (p<0.05). 12 Pantenburg B. reported that a higher proportion of students had negative attitudes towards the overweight as compared to the normal weight individual (98.9% versus 53.7%, p<0.001). 13 Pantenburg B. reported that 49.8% agreed "strongly" and 38.7% "somewhat" to the statement that "overweight is one of the most important health problems in Germany today".…”
mentioning
confidence: 99%